The Development of a Learning Medium Using the Gimkit Application for A1-Level German Reading Skills (Lembaga Pengembangan Kinerja Dosen, 2025)
The aim of this study is to develop an interactive learning medium using the Gimkit application to enhance students’ reading skills at the A1 level. The research follows the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The data were collected from the Netzwerk Neu A1 textbook, specifically Chapter 7 titled “Arbeitsalltag”. Four reading texts were developed into 32 multiple-choice questions and integrated into the Gimkit application. Validation by a content expert resulted in a score of 95.8, and validation by a media expert yielded a score of 90 both classified as “very good”. The findings show that the Gimkit application is a suitable learning medium to support A1-level reading comprehension by making the learning process more engaging, interactive, and motivating.